A simple and sensitive HPLC method for analysis of imipramine in human plasma with UV detection and liquid-liquid extraction: Application in bioequivalence studies - Mahboubeh Rezazadeh; Jaber Emami (Wolters Kluwer Medknow Publications, 2016)
High-performance liquid chromatography (HPLC) methods employing ultraviolet (UV) detector are not sufficiently sensitive to measure the low plasma concentrations following single oral dose of imipramine. Therefore, in the present study a simple, rapid and yet sensitive HPLC method with UV detection was developed and validated for quantitation of imipramine in human plasma samples. An efficient liquid-liquid extraction (LLE) of imipramine from plasma with the mixture of hexane/isoamyl alcohol (98:2) and back extraction of the drug in acidic medium concomitant with evaporation of organic phase allowed the use of UV detector to conveniently measure plasma levels of this compound as low level as 3 ng/ml. Separation was achieved on a μ-Bondapak C 18 HPLC column using sodium hydrogen phosphate solution (0.01 M)/acetonitrile (60/40 v/v) at pH 3.5 ± 0.1 at 1.5 ml/min. Trimipramine was used as the internal standard for analysis of plasma samples. The retention times for imipramine and trimipramine were 4.3 and 5.2 min, respectively. Calibration curve was linear in the range of 3-40 ng/ml using human plasma with the average extraction recovery of 85 ± 5%. Imipramine was found to be stable in plasma samples with no evidence of degradation during three freeze-thaw cycles and three months storage at -70 °C. The current validated method was finally applied in bioequivalence studies of two different imipramine products according to a standard two-way crossover design with a two weeks washout period.